TRANSFORMATION OF REGIONAL PRIORITIES OF REDUCTION OF PREMATURE MORTALITY AS A PREREQUISITE OF ECONOMIC DEVELOPMENT - Zubarev, Nikolai; Zubarev, Yuri (Revista Inclusiones, 2020)
The rationale of this study is the need for economic development of Russia's regions in the conditions of the current economic slowdown caused by external and internal factors. This paper explores changes in regional priorities of reduction of premature mortality in the economic conditions of a growing focus on public health and living standards. The transformation should entail better management decisions and more efficient use of resources, especially the financial resources. The purpose of the study was to determine the current priorities of reducing premature mortality given the economic situation in the region (through the example of the Perm region).